Last among equals: perceptions and prospects of further education trained PGCE holders in the age of 'parity'. Issue 1 (2nd January 2019) - Best, M.; Ade-Ojo, G. O.; McKelvey, C.
ABSTRACT: This study explores how Further Education (FE) lecturers are perceived in secondary school settings and their professional prospects in the context of the UK parity status Act of 2012. Designed as a mixed method research, it sought the views of FE-trained teachers on their experience of working in secondary schools, the perceptions of recruitment agencies that work directly with FE-trained teachers and of mentors in secondary schools within a case study framework. It found that in spite of the widely acclaimed parity status, the prospects of FE-trained teachers of developing their career via the secondary school route were very limited. It also found that secondary school colleagues have a perception of their FE-trained counterparts as less professional than themselves for some reasons, thus raising a form of intra-professional group conflict. The study recommends policy and curriculum intervention in order for the parity condition to fulfil its full potentials.